Relationship between endothelial cell loss and microcoaxial phacoemulsification parameters in noncomplicated cataract surgery - Soliman Mahdy MAE (Dove Medical Press, 2012)
Mohamed AE Soliman Mahdy1,2, Mohamed Z Eid1, Mahmoud Abdel-Badei Mohammed3, Amr Hafez4,5, Jagdish Bhatia21Ophthalmic Department, Al-Hussein University Hospital, Al-Azhar University, Cairo, Egypt; 2Ophthalmic Department, Rustaq Hospital, Rustaq, Sultanate of Oman; 3Research Institute of Ophthalmology, Cairo, Egypt; 4Magrabi Eye and Ear Center, Muscat, Sultanate of Oman; 5Ophthalmic Department, Al-Azhar University Hospital, Assuit, EgyptPurpose: To assess the relationship between postoperative endothelial cell loss and microcoaxial phaco parameters using Ozil IP (Alcon Laboratories, Inc, Fort Worth, TX) in noncomplicated cataract surgery.Methods: In this prospective observational study, 120 consecutive cases of cataract patients with different grades of nuclear hardness underwent microcoaxial phacoemulsification through a 2.2-mm clear corneal incision. An Alcon Infinity Vision System with Ozil IP (Alcon Laboratories) was used with an Ozil torsional handpiece and a Kelman-style 45° phacoemulsification tip. Patients underwent preoperative and postoperative central endothelial cell counts.Results: The study included 120 cases of age-related cataract whose mean age (standard deviation [SD]) was 59.68 years (9.47). There was a highly statistically significant endothelial cell loss (P < 0.001). The endothelial cell loss ranged 11–1149 cells/mm2 with a median (interquartile range) of 386 cells/mm2 (184.5–686 cells/mm2). The percentage of postoperative ECLoss% ranged from 0.48% to 47.8% with a median (interquartile range) of 15.4% (7.2% to 26.8%). A significant positive correlation was found between the ECLoss% and different phaco parameters. The Spearman’s rank-order correlation coefficient values, rho, (ρ) were as follows: CDE (ρ = 0.425), aspiration time (ρ = 0.176), and volume (ρ = 0.278). Also, ECLoss% was significantly correlated with the grade of nuclear opalescence (Kendall’s tau τ = 0.42).Conclusion: Microcoaxial phacoemulsification was efficient in removing noncomplicated cataracts; however a statistically significant endothelial cell loss was noted, especially with increased nuclear hardness. This endothelial cell loss was mostly related to the increased cumulative dissipated energy (CDE), aspiration time, and volume of balanced salt solution used.Keywords: cataract surgery, phacoemulsification, Ozil, endothelial cells, cumulative dissipated energy